Association of Temperament and Acute Stress Responsiveness with Productivity, Feed Efficiency, and Methane Emissions in Beef Cattle: An Observational Study - Llonch, Pol; Somarriba, Miguel; Duthie, Carol-Anne; Haskell, Marie J.; Rooke, John A.; Troy, Shane; Roehe, Rainer; Turner, Simon P. (Frontiers in Veterinary Science, 2016)
The aim of this study was to assess individual differences in temperament and stress response and quantify their impact on feed efficiency, performance and methane (CH4) emissions in beef cattle. Eighty-four steers (castrated males) (Charolais or Luing), were used. Temperament was assessed using two standardised tests: restlessness when restrained (crush score; CS) and flight speed (FS) on release from restraint. Over a 56-d period individual animal dry matter intake (DMI) and weekly BW was measured. Ultrasound fat depth was measured at the end of 56-d. Average daily gain (ADG), feed conversion ratio (FCR) and residual feed intake (RFI) were calculated. After the 56-d test period, animals were transported in groups of six per week to respiration chamber facilities. Blood samples were taken before and 0, 3, 6 and 9h after transport. Plasma cortisol, creatine kinase (CK), glucose and free fatty acids (FFA) were determined to assess physiological stress response. Subsequently, CH4 emissions were measured over a 3-day period in individual respiration chambers. CS (1.7±0.09) and FS (1.6±0.60 m/s) were repeatable (0.63 and 0.51, respectively) and correlated (r=0.36, P<0.001). Plasma cortisol, CK and FFA concentrations increased after transport (P=0.038, P=0.006 and P<0.001, respectively). Temperament (CS) and CK concentration were correlated (r=0.29; P=0.015). The extreme group analysis reveals that excitable animals (FS; P=0.032) and higher stress response (cortisol, P=0.007; FFA, P=0.007 and CK, P=0.003) were associated with lower DMI. ADG was lower in more temperamental animals (CS, P=0.097 and FS, P=0.030). Fat depth was greater in steers showing calmer CS (P=0.026) and lower plasma CK (P=0.058). Temperament did not show any relationship with RFI or CH4 emissions. However, steers with higher cortisol showed poorer feed efficiency (greater FCR and RFI) (P < 0.05) and greater CH4 emissions (P=0.017). In conclusion, agitated temperament and higher stress responsiveness is detrimental to productivity. A greater stress response is associated with a reduction in feed intake which may both increase the efficiency of consumed feed and the ratio of CH4 emissions per unit of feed. Therefore temperament and stress response should be considered when designing strategies to improve efficiency and mitigate CH4 emissions in beef cattle.